Atuação docente em tempos de cibercultura: reflexões sobre ferramentas virtuais e ensino na modalidade EAD via Zoom - Santos, Débora Sandyla de Araújo dos (2021)
The present work aims to present the ItemNet Zoom (MATOS, 2020) as a pedagogical tool used in the context of language teaching in distance learning (DL),also in pandemic times, as well as to understand the importance of the use of digital tools in language teaching.Digital Information and Communication Technologies (DICT) are increasingly being remodeled and modernized, which brings paradigmatic changes regarding people and interpersonal communication interaction.Technological transformations over the last decades have taken place in an accelerated, broad, and profound way, not only in communication but in other areas. This has an impact on society in general, and it would not be different in education.Through such changes, DL has been renewed, becoming an alternative for many students and teachers who wish to study interactively, practically, and without dislocation. However, DL is still a taboo for Brazilian society, which questions the quality of this study option, as if it were inferior to face-to-face teaching. In the Covid 19 pandemic, many institutions started using Zoom and it is the most used tool for people who work from home nowadays. It is a videoconference platform that has several features. It does not only offer video calls but also allows users to write messages and share files with other users with the support of the screen sharing function.This is qualitative research, as it deals with the analysis of processes that take place in the DL context of Spanish classes. Furthermore, it has a reflective approach that considers the possibilities for potential students to interact, monitor, and understand the features of ItemNet Zoom converted into a Virtual Tool not exclusive to Learning (FVNexA). We seek to base our study on theoretical concepts of Matos (2020) that supported the notions of ItemNet and FVNexA. We also used Kleiman's (2008) reflections on literacies and theoretical assumptions of Silva and Láscar-Alarcón (2016), and Leffa and Irala (2014) about foreign language, second language, and additional language. The research contributes to additional language teaching in the DL, especially Spanish, highlighting the importance and effectiveness of the use of FVNexA, such as ItemNet Zoom. In addition, it proposes reflections on literacy and, mainly, on the teacher’s role as a social agent in the construction of meanings. With the study, we were able to see great effectiveness for Spanish language teaching, as well as considerable student participation during remote classes, which provides opportunities for literacy practices using the DICT.